Seroprevalence of Hepatitis A among Thai Population Residing Near Myanmar Border (Journal of Health, Population and Nutrition, 2011)
When compared with Thailand, the seroprevalence of hepatitis A virus (HAV) is extremely high among its neighbouring countries. To investigate the seroprevalence of HAV among the Thai people residing in the border area between Thailand and Myanmar, 308 residents in Umphang, Maesod district, Tak, were recruited. Sera were tested for HAV IgG antibodies by enzyme-linked immunosorbent assay. The overall seroprevalence among the Thai people residing in the border area of Thailand was significantly higher than that among the general Thai population (71% vs 27% respectively, p